Effects of visual impairment on sensory integration and new opportunitiesfor inclusive education - Belyaeva, Ekaterina; Kartashova, Oxana; Sokolaeva, Nadezhda; Snezhko, Zoya; Spichak, Valentina (Bangladesh Journal of Medical Science, 2021)
Objective: Inclusive education aims to offer comprehensive collaborative education to healthy and disabled children. The purpose of the study is to perform a comparative analysis of the learning results in healthy and disabled children from different groups with those who study remotely, and a similar analysis between students of higher education institutions. Methods: The study was conducted in 2018–19 in Moscow, Russia, involving 150 students with disabilities and 397 healthy students. Consideration was given to academic performance, psychophysical development and speech development. Results and Discussion: Among students with healthcare nosologies, students with vision impairments are considered the most promising. The number of underachievers is 4.9 times lower than their peers (p 0.001).The greatest success in e-learning was among students with health nosologies relative to a similar group of children. Conclusions: The number of outstanding students in the group with visual impairments exceeds those in the control group by 1.5 times (p≤0.05). Of the students with health nosologies, the most promising group is visually impaired students. High academic performance of students with visual impairments and disordered motor activity provides them with the opportunity to practice comprehensive education at universities, including inclusive education, which corresponds to current worldwide trends. Bangladesh Journal of Medical Science Vol.20(4) 2021 p.801-808